Assessment of pre-operative and post-operative functional outcome of Mini Open Carpal Tunnel Release in Carpal Tunnel Syndrome - Singh , Janith Lal; Maharjan, Basanta; Bajracharya , Aayush; Shrestha, Shriraj; Bhandari, Pramod; Shrestha , Shefali (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Carpal tunnel syndrome (CTS) is the most common peripheral entrapment neuropathy, causing pain, functional impairment, and reduced quality of life. Mini-open carpal tunnel release (mOCTR) is a minimally invasive alternative to conventional surgery, offering quicker recovery and fewer complications. Methods: A prospective pre-post study was conducted at KIST Medical College and Teaching Hospital, Nepal, from August 2024 to July 2025. Adult CTS patients undergoing mOCTR were included. Functional outcomes were assessed preoperatively and at 2 and 6 weeks postoperatively using the Boston Carpal Tunnel Questionnaire (BCTQ) for Symptom Severity Score (SSS) and Functional Status Score (FSS), and the Visual Analogue Scale (VAS) for pain. Data were analyzed in SPSS v26, with p < 0.05 considered significant. Results: Twenty-seven patients were studied, mean age 50.1 years (SD ±9.7), with 24 (88.9%) females. Right-hand dominance was seen in 25 (92.6%), and right-hand involvement in 18 (66.7%). Housewives comprised 18 (66.7%) and desk job workers 5 (18.5%). Significant postoperative improvements were observed. Mean SSS reduced from 4.13 to 2.23 at 2 weeks and 1.43 at 6 weeks (p < 0.01). FSS declined from 3.93 to 2.31 and 1.39 at 2 and 6 weeks (p < 0.01). VAS pain scores decreased from 7.33 to 3.81 and 1.70 (p < 0.01). No major complications occurred; mild scar tenderness was seen in 2 (7.4%) patients, resolving spontaneously. Conclusion: Mini-open carpal tunnel release is a safe and effective procedure with excellent functional outcome.